Ground Fault Protection methods for Distribution Systems - Tavares, Hugo Ricardo dos Santos; Nogueira, Teresa Alexandre (Neutro à Terra, 2016)
The system grounding method option has a direct influence on the overall performance of the entire medium voltage network as well as on the ground fault current magnitude. For any kind of grounding systems: ungrounded system, solidly and low impedance grounded and resonant grounded, we can find advantages and disadvantages. A thorough study is necessary to choose the most appropriate grounding protection system. The power distribution utilities justify their choices based on economic and technical criteria, according to the specific characteristics of each distribution network. In this paper we present a medium voltage Portuguese substation case study and a study of neutral system with Petersen coil, isolated neutral and impedance grounded.